Helicoidal surfaces with Δ ᴶ ᵣ = Ar in 3-dimensional Euclidean space - SENOUSSI, Bendehiba; BEKKAR, Mohammed (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
In this paper we study the helicoidal surfaces in the 3-dimensional Euclidean space under the condition ΔJ r = Ar; J = I; II; III; where A = (aij) is a constant 3 χ 3 matrix and ΔJ denotes the Laplace operator with respect to the fundamental forms I, II and III. Mathematics Subject Classification (2010): 53A05, 53A07, 53C40.